The Effect of Sales Promotion, Security and Convenience on Gopay E-Wallet Customer Satisfaction Case Study on Gopay Customers In Medan City) - Karmila Sari; Nur Ahmadi Bi Rahmani; Mawaddah Irham (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aims to determine the influence of sales promotion, security and covenience on Gopay e-wallet customer satisfaction partially and simultaneously. This research uses quantitative research methods. The population in this study are people who use Gopay e-wallets in Medan City and a sample of 100 respondents is taken. Sampling was carried out by non probability sampling and using purposive sampling method. The data collection technique used a questionnaire which was measured using a Likert scale. The data analysis technique used in this research is descriptive test, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing. Tests were carried out using SPSS ver 20. The results showed that sales promotion, security and convenience have a positive and significant impact on Gopay e-wallet customer satisfaction. The results of the t test prove that partially the sales promotion, security and convenience variables affect Gopay e-wallet customer satisfaction. From the results of the F test it proves that the sales promotion, security and convenience variables simultaneously have a significant effect on Gopay e-wallet customer satisfaction with the F-count value greater than the F-table.